The role of education and educational–occupational mismatches in decisions regarding commuting and interregional migration from eastern to western Germany - Melzer, Silvia Maja; Hinz, Thomas (Demographic research, 2019)
This paper investigates commuting and interregional migration from eastern to western Germany, and asks, first: Who chooses to migrate and who chooses to commute? Second: Does commuting serve as a stepping-stone or as a long-term alternative to migration? And third: What role does education and educational-occupational mismatch play in those choices? We use the Socio-Economic Panel data from 1992 to 2013 and multilevel multinomial logit models with random effects, as well as cross-classified multilevel logit with random effects. People with higher education are more likely to migrate than to remain immobile or to commute, while people who have spent less time in education are more likely to commute than to remain immobile or to migrate. Educational-occupational mismatches reduce the likelihood of migration for both men and women, but they reduce the likelihood of commuting only for men. For women, educational-occupational mismatches increase the likelihood of commuting. Moreover, commuting serves as a stepping-stone to migration, rather than as a long-term alternative to it, especially for the highly educated.